A comparative exploration of FreeBSD bug lifetimes - BOUGIE, Gargi (Institutional Knowledge at Singapore Management University, 2010)
In this paper, we explore the viability of mining the basic data provided in bug repositories to predict bug lifetimes. We follow the method of Lucas D. Panjer as described in his paper, Predicting Eclipse Bug Lifetimes. However, in place of Eclipse data, the FreeBSD bug repository is used. We compare the predictive accuracy of five different classification algorithms applied to the two data sets. In addition, we propose future work on whether there is a more informative way of classifying bugs than is considered by current bug tracking systems.